PENGGUNAAN METODE SAS BERBANTUAN KARTU KATA BERGAMBAR TERHADAP KEMAMPUAN MEMBACA PESERTA DIDIK KELAS I DI SEKOLAH DASAR - Nabila Intan Rahayu; Aas Saraswati; Feby Inggriyani (STKIP Subang, 2023)
This study aims to determine the effect of using the SAS method assisted by picture word cards on the beginning reading ability of grade 1 students in elementary schools. In this study using a quantitative approach with a research design using a quasi-experimental or quasi-experimental design. The samples in this study were class I-A, which consisted of 25 students as class and class I-B, which consisted of 25 students as the control class. The data collection technique used in this study is through tests and observations. The tests used are pre-test and ¬post-test. Based on the research results, the experimental class obtained an average pretest score of 45.53 with an average posttest score of 86.12. Meanwhile, the average value of the control class pretest was 44.86 and the average posttest value of the control class was 66.96. The results of the tests carried out by researchers in the experimental class and control class, it can be concluded that the posttest score was found to be greater than the pretest, which means that students' initial reading ability increases. The researcher used an independent test sample t test to find the effect of the SAS method assisted by picture word cards on the beginning reading ability of first grade elementary school students. It is known that the calculated t value is 16.139 with a sig value of 0.000 <0.05, which means that there is a significant influence on the initial reading ability of first grade elementary school students in the experimental class and the control class. Then in accordance with the decision making that has been determined then that Ho is rejected and Ha is accepted. Thus the researchers concluded that there was an effect of using the SAS method assisted by picture word cards on the initial reading ability of grade 1 students in elementary schools.